Comparison of oral antiviral therapy with valacyclovir or acyclovir after penetrating keratoplasty for herpetic keratitis. Issue 9 (23rd July 2008) - Goldblum, D; Bachmann, C; Tappeiner, C; Garweg, J; Frueh, B E
Abstract : Aims: To compare the outcome of prophylactic oral valacyclovir (VAL) or oral acyclovir treatment (ACV) in patients having undergone penetrating keratoplasty for herpetic keratitis (HK). Methods: All patients having received a penetrating keratoplasty for HK and being treated postoperatively with either oral VAL or oral ACV (inclusion period from 12/97 to 3/06 and 5/92 to 9/96, respectively) were retrospectively evaluated. Records were analysed for postoperative reactivation of recurrent HK, graft rejection, endothelial cell loss, central corneal thickness and visual acuity after a follow-up of up to 5 years. Results: Twenty patients received VAL and were compared with 19 patients being treated with ACV. Two patients developed clinical signs of recurrent herpetic disease in the VAL group compared with three patients in the ACV group. Two patients from both groups each developed an irreversible graft failure. Best corrected visual acuity improved in both treatment groups from baseline (logMAR) −1.97 (VAL), −1.47 (ACV) to −0.85, −0.72, respectively, at the 1-year follow-up and slightly deteriorated after 5 years in the ACV group (−0.71 VAL vs −1.14 ACV). Conclusion: Prophylactic oral VAL treatment is at least as effective as ACV in preventing recurrence in patients who underwent corneal transplantation for HK. The tolerability of the two drugs is similar, but the dosing for VAL might be more comfortable for patients.